(untitled) (Theatrum historiae, 2007)
After the revolution in 1905-1906, Russian monarchy had to reinforce its power. There were many national and historical celebrations before 1914, but the Tercentenary of the Romanov Dynasty in 1913 was the largest. The celebration of the Romanov dynasty had a great symbolic importance. Mikhail Fyodorovich Romanov was elected Tsar in 1613 and with his coronation the same year, the Time of Troubles (smuta) was put to an end. For Nicholas II and the conservative monarchists, there was a clear parallel between the deep political crisis at the beginning of the 17th century and the recent events. The Tercentenary celebrations had to resurrect the national spirit and to show that there was a bound between the common people and the Tsar. Their character was influenced by official state ideology: „orthodoxy, autocracy and nationalism“. The celebrations took place in St. Petersburg in February, in some Volga towns and in Moscow in May 1913. The tsarist family was in the center of the festivities, and Nicholas II wanted to make them the „non-party celebrations“. But the presence of ultra-right organizations in the festivities was clear, at least in St. Petersburg. In any case, Nicholas II was strongly impressed by the visit in Volga towns (Vladimir, Nizhnii Novgorod, Kostroma, Yaroslavl, Rostov etc.) and by the opportunity to meet the people, especially the peasants. He thought he had the people‘s loyalty and support, and believed the society was prevalently conservative. It was a great illusion, for most of the population remained indifferent to the celebrations, and the idea of popular monarchy, so much favored by tsar, was not attractive to them. Only the ultra-right organizations were ardent supporters of the autocratic model of monarchy.